2001
DOI: 10.1038/91008
|View full text |Cite|
|
Sign up to set email alerts
|

Antiproliferative activity of ecteinascidin 743 is dependent upon transcription-coupled nucleotide-excision repair

Abstract: While investigating the novel anticancer drug ecteinascidin 743 (Et743), a natural marine product isolated from the Caribbean sea squirt, we discovered a new cell-killing mechanism mediated by DNA nucleotide excision repair (NER). A cancer cell line selected for resistance to Et743 had chromosome alterations in a region that included the gene implicated in the hereditary disease xeroderma pigmentosum (XPG, also known as Ercc5). Complementation with wild-type XPG restored the drug sensitivity. Xeroderma pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
258
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(290 citation statements)
references
References 33 publications
17
258
1
4
Order By: Relevance
“…The resistance to trabectedin of the colorectal carcinoma ER5 cell line (derived from the HCT116 cells) is associated with a loss of heterozygosity at 13q33, where the gene encoding for XPG is located. Sequential analysis of the XPG gene showed an insertion of adenine at codon 240, which resulted in a stop codon at position 243 (5,30). Another mechanism associated with trabectedin's resistance has been described in human surgically resected chondrosarcoma cells (CS-1; ref.…”
Section: Resistance To Trabectedinmentioning
confidence: 99%
“…The resistance to trabectedin of the colorectal carcinoma ER5 cell line (derived from the HCT116 cells) is associated with a loss of heterozygosity at 13q33, where the gene encoding for XPG is located. Sequential analysis of the XPG gene showed an insertion of adenine at codon 240, which resulted in a stop codon at position 243 (5,30). Another mechanism associated with trabectedin's resistance has been described in human surgically resected chondrosarcoma cells (CS-1; ref.…”
Section: Resistance To Trabectedinmentioning
confidence: 99%
“…This type of interaction differs from that observed for other DNA-binding antitumor drugs and could account for some of the distinctive pharmacologic features of trabectedin, such as the potent and rapid inhibition of activated but not constitutive transcription (3,4) and the atypical response detected in cells with deficiencies in nucleotide excision repair (NER). In this latter respect, whereas all known DNA-interacting drugs are either more effective or equally effective in NERdeficient cells relative to their NER-proficient counterparts (5 -8), trabectedin is paradoxically less cytotoxic in NERdeficient cells (9 -12), particularly in those harboring a deleterious mutation in the XPG endonuclease (11,13). On the other hand, experimental evidence from different laboratories has shown that both yeast mutants with gene deletions in the RAD52 epistasis group [e.g., Saccharomyces cerevisiae rad52D (9) and Schizosaccharomyces pombe rad51D and rad54D cells (13,14)] and mammalian cells deficient in XRCC3, BRCA2, RAD51C, and XRCC2 (15) are much more sensitive to trabectedin than their normal counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides inhibition of transcription, the specific and stable structures formed by TFO with genomic sites might induce cell cycle arrest. 26 In this study, we utilized this antigene strategy to target survivin in human lung carcinoma A549 cells and our results suggest that the triplex technique is a promising tool for anticancer therapeutics.…”
mentioning
confidence: 85%